Preassembled capsids of type D retroviruses contain a signal sufficient for targeting specifically to the plasma membrane. - Rhee, S S (1990)
The capsids of Mason-Pfizer monkey virus (M-PMV), an immunosuppressive type D retrovirus, are preassembled in the infected cell cytoplasm and are then transported to the plasma membrane, where they are enveloped in a virus glycoprotein-containing lipid bilayer. The role of viral glycoprotein in intracellular transport of M-PMV capsids was investigated with a spontaneous mutant (5A) of M-PMV, which we show here to be defective in envelope glycoprotein biosynthesis. DNA sequence analysis of the env gene of mutant 5A reveals a single nucleotide deletion in the middle of the gene, which results in the synthesis of a truncated form of the envelope glycoprotein. Evidence is presented showing that the mutant glycoprotein is not expressed at the cell surface but is retained in the endoplasmic reticulum. Normal levels of gag-pro-pol precursor polyproteins are made and processed in mutant genome-transfected cells, and high levels of noninfectious particles lacking viral glycoprotein are released with normal kinetics into the culture medium. No intracisternal budding of capsids is observed. We conclude that viral glycoprotein is required neither for targeting preassembled capsids of M-PMV to the plasma membrane for final maturation nor for the budding process. Since the presence or absence of M-PMV glycoprotein at the site of budding does not affect the efficiency or kinetics of the targeting process, the preassembled capsid of M-PMV, in contrast to those of intracisternal type A particles, appears to have an intrinsic signal for intracellular transport to the plasma membrane.